1990
DOI: 10.3109/10826089009053166
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Disciplinary Actions Among 300 Nurses

Abstract: A survey of 300 U.S. nurses recovering from alcohol and other drug dependency was conducted to describe the effect of drug use on job performance and related disciplinary actions. Subjects reported experimentation with or dependence on a variety of drug categories. Many visible effects on job performance were reported but only 23% reported disciplinary action against their nursing licenses. Females and older nurses were more often dependent on alcohol, while younger nurses and males reported narcotic dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…On the other hand, there remains a very strong stigma in relation to the abuse of psychoactive substances by healthcare professionals, especially given the ethical and employment issues, which constitute a potential threat of job loss. Furthermore, the social pressure on female professionals causes this segment to remain as an invisible population among users of alcohol and/or other drugs (19) . Another relevant result refers to smoking, since tobacco use was a predictor (OR 8.9) for the problematic consumption of alcohol in the sample (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there remains a very strong stigma in relation to the abuse of psychoactive substances by healthcare professionals, especially given the ethical and employment issues, which constitute a potential threat of job loss. Furthermore, the social pressure on female professionals causes this segment to remain as an invisible population among users of alcohol and/or other drugs (19) . Another relevant result refers to smoking, since tobacco use was a predictor (OR 8.9) for the problematic consumption of alcohol in the sample (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The abusive use of these substances, is frequently linked to bad or unsafe use of these controlled drugs at healthcare services (18) . A study conducted with 300 nurses enrolled in treatment programs showed that a sixth of these professionals had changed workplace (generally, through internal transfer at the same hospital) in order to have easier access to drugs in the workplace (19) . On the other hand, there remains a very strong stigma in relation to the abuse of psychoactive substances by healthcare professionals, especially given the ethical and employment issues, which constitute a potential threat of job loss.…”
Section: Discussionmentioning
confidence: 99%
“…Programs vary considerably from state to state, but typically nurses are placed on probation or their license is suspended or revoked (LaDuke 2000). If they are on probation, they may be allowed to work under supervision (Sullivan et al 1990). Although some programs may require treatment as a condition of reentry into the field (Mike Harkreader, personal communication, January, 2009), the disciplinary process focuses on discipline rather than advocating for nurses or encouraging rehabilitation and reentry into the profession (Quinlan 1994;Sullivan et al 1990).…”
Section: The Traditional Disciplinary Approach Vs Alternative Approamentioning
confidence: 99%
“…For the next 80 years, nurses so afflicted were viewed as morally weak and not fit to practice. Correspondingly, most regulatory boards of nursing imposed discipline on the chemically dependent nurse, which invariably led to probation, suspension, or permanent revocation of the license (LaDuke 2000; National Council of State Boards of Nursing 1987; Sullivan et al 1990). Generally speaking, the primary purpose of a disciplinary approach is to protect the public rather than rehabilitate the nurse (Sullivan et al 1990).…”
Section: History Of Addiction In the Nursing Professionmentioning
confidence: 99%
“…It has been estimated that the process of investigation followed by a formal hearing to determine disciplinary action may take from eight months to three years for resolution and, as the focus is on discipline, there is little attempt to advocate for the individual, provide treatment or rehabilitation services, or follow outcomes (Sullivan, Bissell, & Leffler, 1990). With alternative to discipline responses, when there is reason to believe that the use of substances are affecting professional performance, the authority (e.g.…”
Section: Policy Alternativesmentioning
confidence: 99%